How well do Radiologic Assessments of Truncal and Shoulder Balance Correlate With Cosmetic Assessment Indices in Lenke 1C Adolescent Idiopathic Scoliosis?. Issue 8 (October 2016) - Sharma, Shallu; Andersen, Thomas; Wu, Chunsen; Sun, Haolin; Wang, Yu; Hansen, Ebbe S.; Bünger, Cody E.
Abstract : Study Design: A correlation study. Objective: The primary objective was to determine the correlation between radiologic and cosmetic indices of trunk and shoulder balance before and after scoliosis surgery in Lenke 1C adolescent idiopathic scoliosis and to determine whether postoperative trunk shift is affiliated with worsening of the patients' cosmesis. Summary of Background Data: Achieving a symmetrical appearance with truncal and shoulder balance is of prime importance to adolescent idiopathic scoliosis patients and their surgeons. However, surgeons prefer radiographic indices rather than measures of patients' clinical appearance. If radiographic indices are to be considered accurate depictions of the patient's cosmesis, radiologic and cosmetic indices must necessarily exhibit high association. Methods: Radiographic and cosmetic indices of trunk and shoulder balance, along with posterior trunk symmetry index, were measured preoperatively and 3 months postoperatively in 33 Lenke 1C scoliosis patients. Pearson correlation analysis was performed. Paired t test was used to determine significant changes in radiographic and cosmetic indices after surgery. Independent-sample t test was used for all intergroup analyses in trunk shift and no-trunk-shift groups. Results: Correlation coefficients between radiologic and cosmetic indices ranged between −0.63 and 0.70 with thoracic apical vertebra-central sacral vertical line (AV-CSVL) distance and first rib angle showing consistent correlations with cosmetic trunk and cosmetic shoulder balance indices. Trunk shift, a postoperative iatrogenic phenomenon, was seen in 19 (58%) patients. These patients had higher preoperative thoracic AV-CSVL translation, thoracic apical vertebra-first thoracic vertebra (AV-T1) translation, thoracic deformity correction rate, AV-T1 correction rates, and shorter fusions compared with the no-trunk-shift group. Posterior trunk symmetry index worsened in trunk shift group and improved significantly (−7.94 vs. 16.53) in no-trunk-shift group. Significant association ( P =0.004) was seen between radiographic and cosmetic trunk shift. Conclusions: Radiographic indices can only minisculely ( r ⩽0.7) reflect cosmetic deformity in Lenke 1C scoliosis, which emphasizes not only the vulnerability of overreliance on radiographic indices but also the vital importance of clinical cosmetic evaluations. In particular, cosmetic shoulder height and angle are not represented by radiographic indices. However, radiograph trunk shift was significantly associated with cosmetic trunk shift in cosmetic pictures.